Analysis of Female Audience Receptions towards Infidelity in the "Ipar adalah Maut" Movie - Islami, Farina; Meok, Irene Aprilya (Jurnal Komunikasi, 2024)
Film is a medium of communication that is in great demand today, the impressions shown in movies have different meanings for each audience. Films depicting the issue of infidelity tend to highlight various negative impacts, the audience as an active audience certainly acts also as a producer of meaning. The purpose of the study was to analyze how the female audience's reception of infidelity that occurred in the film sister-in-law is death. The method used is Stuart Hall's reception analysis with a qualitative approach. Data collection was done by interviewing five informants. The results showed that four informants were in the dominant position, one informant was in the negotiation position and there were no informants in the opposition position. The implications of the research can reveal how women interpret and respond to representations packaged by film mass media, which in turn can increase self-awareness and strengthen advocacy regarding fairer and more empowering gender representations in the media.